Effective Antimicrobial Materials Based on Low-Density Polyethylene (Ldpe) with Zinc Oxide (Zno) Nanoparticles - Zapata-Ramirez, P; Canales-Arévalo, D; Cament-Riveros, A (Elsevier Ltd, 2019)
Effective antimicrobial polymeric nanocomposites were prepared with low density polyethylene (LDPE) and zinc oxide nanoparticles by melt compounding. These nanoparticles (∼17 nm) obtained by the sol–gel method, were used both as-synthesized and modified organically with oleic acid (Mod-ZnO). Young s modulus increased ∼15 and 18% for LDPE/ZnO and LDPE/Mod-ZnO, respectively, compared to neat LDPE. When these composites were irradiated with white light, they showed an increase with nanoparticle incorporation, and the antimicrobial properties against E. coli were ∼96–99%. The release of the Zn cations was related to the antimicrobial properties. These nanocomposites are attractive for use as food packaging without external irradiation. © 2019 Elsevier Ltd